1999
DOI: 10.1111/j.1464-0597.1999.tb00060.x
|View full text |Cite
|
Sign up to set email alerts
|

When Earthquake Damage is Seen as Preventable: Attributions, Locus of Control and Attitudes to Risk

Abstract: Divers travaux ont montrC que le locus of control et les attitudes face au risque dkterminaient les conduites devant les dangers de la nature. Deux ttudes ont tent6 de determiner lequel de ces deux facteurs Ctait le meilleur pridicteur des jugements et de la prkparation concernant les tremblements de terre. Ces notions ont 6t6 relikes h des modkles de l'attribution des digits causCs par les tremblements de terre, par l'examen de la spCcificitC des destructions sur les attributions et la complexit6 des explicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
89
0
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(94 citation statements)
references
References 34 publications
4
89
0
1
Order By: Relevance
“…Psychologically, fatalism entails the perception that there is little or nothing one can do to avoid or protect oneself from risk, and that the locus of control over life events is external to oneself (McClure et al, 1999). Specifically, earthquake fatalism implies that the causes of damage are attributed to the force of the earthquake alone, rather than to building design or other controllable factors (McClure et al, 2001).…”
Section: Fatalismmentioning
confidence: 99%
See 1 more Smart Citation
“…Psychologically, fatalism entails the perception that there is little or nothing one can do to avoid or protect oneself from risk, and that the locus of control over life events is external to oneself (McClure et al, 1999). Specifically, earthquake fatalism implies that the causes of damage are attributed to the force of the earthquake alone, rather than to building design or other controllable factors (McClure et al, 2001).…”
Section: Fatalismmentioning
confidence: 99%
“…One motivating force is knowledge that leads to the belief that one can control the outcome of the earthquake, that is, self-efficacy. McClure and colleagues (Cowan et al 2002;McClure et al, 1999McClure et al, , 2001McClure et al, , 2007a have shown that certain characteristics of information about earthquake damage, as presented via mass media reports for example, can shape attitudes towards preventability. Specifically, reports that provide accurate, rate-based information about why one type of building withstood ground-shaking whereas another type collapsed enables people to understand that building design is a major cause of losses, allowing them to infer more easily that losses are controllable.…”
Section: Individual Attitudes Towards Controlmentioning
confidence: 99%
“…According to Lamontagne and La Rochelle (2000), seismologists should follow psychological courses to help and support the public's emotional reactions before or after an earthquake. Scientists should also participate in communication plans which include concrete facts about earthquakes, to anticipate the event and its associated anxiety (Lamontagne, 1992;McClure et al, 1999). Science can at least promote up-to-date scientific ideas instead of fakes and rumours disseminated by local beliefs or the internet.…”
Section: Discussionmentioning
confidence: 99%
“…Рустамли и Каранци (Rüstemli, Karanci, 1999) су утврдили да људи са вишим нивоима образовања имају мање страха, више личне контроле и чешће користе социјалну помоћ. Док, с друге стране, постоје студије у којима се наглашава да не постоји директна веза између поседовања информација о опасностима и припремних мера (Ballantyne, 2000;McClure et al, 1999;Mileti, Fitzpatrick, 1992). Танака је спровео квантитативно истраживање у коме је анкетирао становнике одабраних градова у Јапану и Калифорнији.…”
Section: фактори утицаја на припремљеност за земљотресеunclassified